2021
DOI: 10.1177/0897190021999781
|View full text |Cite
|
Sign up to set email alerts
|

Unprovoked Dystonic Reaction in a Child Taking Long-Term Methylphenidate

Abstract: In this report, we discuss the case of a 9-year-old male with Attention Deficit Hyperactivity Disorder (ADHD) on long-term methylphenidate and guanfacine who experienced acute orofacial dystonia that resolved immediately with the administration of benztropine. Current literature describes various cases of methylphenidate-induced dystonia, but ours appears to be the first reported instance of spontaneous dystonia without a recent change in dose or medication change. This may suggest the possibility of methylphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…4,5 There is only one other case of tardive dystonia that we are aware with MPH. 3 In that case, Pagliaro and et al reported emergence of an episode of tardive dystonia in 9 years old male patient with ADHD who had been treated with ER MPH 27 mg/day and guanfacine 1 mg/day, who was treated with benztropine 1.5 mg IM and diphenhydramine 25 mg PO. 3 Their Naranjo score was 4 ("possible").…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…4,5 There is only one other case of tardive dystonia that we are aware with MPH. 3 In that case, Pagliaro and et al reported emergence of an episode of tardive dystonia in 9 years old male patient with ADHD who had been treated with ER MPH 27 mg/day and guanfacine 1 mg/day, who was treated with benztropine 1.5 mg IM and diphenhydramine 25 mg PO. 3 Their Naranjo score was 4 ("possible").…”
Section: Discussionmentioning
confidence: 97%
“…Rare dystonic reactions with MPH were previously reported. [3][4][5] Most of those involved acute cases which emerged after treatment initiation/ increase in dose or with MPH discontinuation while continuing to use antipsychotics. 4,5 There is only one other case of tardive dystonia that we are aware with MPH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations